Controversies in the treatment of skin neoplasias - Sternemann, Maria; Wiegel, Thomas; Geilen, C. G.; Orfanos, C. E. 1936-; Hinkelbein, Wolfgang 1948- (Karger, 2006)
Based on the 8th International Symposium on Special Aspects of Radiotherapy held in Berlin in 2004, this volume discusses current controversial topics in the management of skin neoplasias with special emphasis on radiotherapeutic and dermatologic strategies. Following an interdisciplinary approach, it presents the latest diagnostic and therapeutic developments for cutaneous lymphoma, basal and squamous cell carcinomas, and malignant melanoma. Two further chapters focus on more uncommon tumors such as Kaposi's sarcoma and Merkel cell carcinoma. A detailed overview of skin reactions to radiotherapy is given, and new trends in staging procedures are discussed .In summary, this book will not only be a valuable update for dermatologists and radiation oncologists, but will also provide useful insights for anyone involved in the care of patients with skin neoplasias
8th International Symposium on Special Aspects of Radiotherapy, Berlin, September 2004 ; a valuable update for dermatologists and radiation oncologists
Keywords: Radiology; Dermatology; Oncology; Pathology; Plastic Surgery; Radiobiology; Surgery; Strahlentherapie; Hautkrebs; Konferenzschrift -- 2004 -- Berlin